2016
DOI: 10.1007/s00417-016-3535-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravitreal bevacizumab for macular edema following branch retinal vein occlusion stratified by baseline visual acuity

Abstract: In ME following BRVO, baseline visual acuity correlates with macular ischemia and baseline CRT. Intravitreal bevacizumab treatment results in significant anatomical and functional improvement regardless of baseline visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…If VA improvement and CRT decrease <30%, two further IVB injections administered at 6 weeks intervals. Naive 55 58 (9.2) 50.9 Prospective, multi-centre 12 Kim et al a [ 93 ] South Korea Bevacizumab 1.25 mg (low BCVA group) Single injection then monthly PRN regimen. Patients with baseline BCVA < 20/200 were in this arm.…”
Section: Resultsmentioning
confidence: 99%
“…If VA improvement and CRT decrease <30%, two further IVB injections administered at 6 weeks intervals. Naive 55 58 (9.2) 50.9 Prospective, multi-centre 12 Kim et al a [ 93 ] South Korea Bevacizumab 1.25 mg (low BCVA group) Single injection then monthly PRN regimen. Patients with baseline BCVA < 20/200 were in this arm.…”
Section: Resultsmentioning
confidence: 99%
“…This result is comparable to the result found in Korea where the mean age was 53.07±9.06 years among patients with BRVO with ME in whom comparative study of the visual outcome of the natural course group, IVA group, and intravitreal triamcinolone group was done. (11)…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the pre-operative BCVA was the best predictor of final visual outcome ( Table 2). Kim et al (2017) and Yunoki et al (2012) also commented that the baseline visual acuity helped to predict the final visual outcome. However, both the studies were done in cases with BRVO.…”
Section: Discussionmentioning
confidence: 99%